Kajian manajemen mutu terpadu pendidikan di perguruan tinggi - Supangat, Supangat; Jaelani, M Syahran; Harja, Harlina; Delastri, Ilta (Journal of Educational Administration and Leadership, 2023)
This research aims to analyze the concept and implementation of Integrated Quality Management (IQM) within the realm of higher education institutions. The research method employed here is a systematic literature review to construct a comprehensive overview of IQM within the context of higher education. The analysis technique involves article retrieval, text review, data categorization, and synthesis of relevant information. The research findings indicate that IQM in higher education involves the integration of various management components to enhance the quality of education, teaching, research, and institutional governance. In conclusion, the implementation of IQM can strengthen the overall quality of higher education institutions, but it requires a well-integrated approach among various elements to achieve these objectives.